Investigation of Mode I fracture toughness of red Verona marble after thermal treatment - Daniela Scorza; Andrea Carpinteri; Giovanni Fortese; Sabrina Vantadori; Daniele Ferretti; Roberto Brighenti (Fracture and Structural Integrity)
The present paper aims to assess the effect of freeze/thaw cycles on fracture behaviour of a natural stone: the red Verona marble. A wide variety of specimen types and methods to determine Mode I fracture toughness of natural stones are available in the literature and, in this context, the model originally proposed for plain concrete, i.e. the Two-Parameter Model (TPM), is adopted. Such a method is able to take into account the slow nonlinear crack growth occurring before the peak load, typical of quasi-brittle materials, with the advantage of easy specimen preparation and simple test configuration. In the present paper, the atmospheric ageing is simulated by means of thermal pre-treatments consisting of freeze/thaw cycles. Experimental tests are carried out using three-point bending Single-Edge Notched (SEN) specimens, according to the TPM procedure. The effects of thermal treatment on both mechanical and fracture parameters are examined in terms of elastic modulus and fracture toughness, respectively